Influence of dietary phytogenic feed additives on lactation performance, methane emissions and health status of Murrah buffaloes (Bubalus bubalis). (22nd January 2021) - Dey, Avijit; Attri, Kiran; Dahiya, Satbir S; Paul, Shyam S
Abstract: BACKGROUND: Several feed additives have been used in recent past to reduce enteric methane production in ruminants. But most of them also inhibit feed digestibility and rumen fermentation, thereby lowering animal performance. Phytogenic feed additives are gaining importance owing to their safety in regard to human health issues. The present study examined the effect of dietary supplementation of phytogenic feed additive containing a blend of poplar ( Populus deltoides ) and eucalyptus ( Eucalyptus citriodora ) leaves on feed utilization, milk production, methane emissions and health status of Murrah buffaloes ( Bubalus bubalis ). RESULTS: The daily milk yield, 6% fat corrected milk yield, and fat–protein corrected milk yield were increased ( P < 0.05) in phytogenic composite feed additive (PCFA)‐supplemented buffaloes. A decrease (37.3%) in methane concentration in exhaled air of supplemented buffaloes was evident. The digestibility coefficient of dry matter, organic matter and neutral detergent fibre was increased ( P < 0.05) in PCFA‐fed buffaloes without affecting feed intake. Total digestible nutrient content of the ration fed to buffaloes of the PCFA group was significantly ( P < 0.05) increased. The buffaloes fed PCFA exhibited an enhanced cell‐mediated and humoral immune response. CONCLUSION: A discernible positive impact was evident on overall performances and health status along with lowered methane production of buffaloes fed (15 g kg −1 dry matter intake) a blend of phytogenic feed additive composed of leaves of poplar ( P. deltoides ) and eucalyptus ( E. citriodora ). © 2021 Society of Chemical Industry